Perception towards safety and health in the agriculture sector and associated factors among older farmers in Perak and Johor, Malaysia - Latif, Nabilah (2014)
Safety and health problems at the workplace have always been a major issue especially to the high risk and dangerous hazards exposure like in the agricultural sector. Previous researchers found that understanding the perception on workplace safety and health among the farmers lead to identification of factors related to process of accidents and somehow reduces the problems. This cross sectional study was designed to determine the workplace safety and health problems and concurrently ascertain the association between older farmer‟s perception on workplace safety and the risk factors involved among them. As the states of Perak and Johor contribute the highest number of district farmers association, a total of 164 older farmers age 45 years old and above were chosen from five associations from each states based on proportionate sampling, giving a response rate of 97.6%. A set of questionnaire which comprised of respondent‟s demographic background, inclusive of questionnaire to identify specifically the safety and health problem together with a validated questionnaire of 50-item Work Safety Scale (WSS) which had a good Cronbach alpha of 0.887 to 0.993 to measure perception on safety was used for data collection during the face to face interview. Data was then analyzed using SPSS Version 19. Respondents were grouped into low and high perception group based on their total scores on the ten items of each of the WSS. It was found that, majority of respondents were male (78.0%), married (87.2%), possess primary education (49.4%), land owners (62.2%), have been working more than 30 years in agricultural sectors (66.5%) and low income earners of less than RM3,000 (84.1%). Vision and musculoskeletal problems were the major health problems contributing approximately 63% and 60% respectively while for safety problems, fall contributed the highest percentage (39.6%). Five factors were found to be significantly associated with safety problems; age (χ2=18.871,p<0.01), education level (χ2=11.699,p=0.003), job tenure (χ2=20.131,p<0.01), monthly income (χ2=5.748, p=0.017), and the perception on job safety (χ2=6.898,p=0.009) while for health problems, four factors were significantly associated such as age (χ2=7.771,p=0.021), job categories (χ2=5.875,p=0.015), perception on job safety (χ2=5.332,p=0.021) and coworkers safety (χ2=5.884,p=0.031). Further analysis using logistic regression test for the significant variables showed the entire above factor were significant towards safety problem where age (p<0.01) and job tenure (p=0.014) was more likely to contribute to safety problems (age; OR=8.497, 95% CI: 3.532–20.446, job tenure; OR=4.016, 95% CI: 1.318–12.235). However for health problem, age was non significant factors (OR=3.151, 95% CI: 0.814–12.198) while job category (OR=0.346, 95% CI= 0.118-0.932), perception on job safety (OR=0.200, 95% CI= 0.040-0.990) and perception on coworkers safety (OR=0.409, 95% CI= 0.192-0.868) were found to be the protective factors for health problems. Consistent with previous studies, this research has shown that age is an important risk factor especially for safety problems among older farmers. In conclusion, safety and health problems among older farmers had mixed association with age, job tenure, income, perception on job safety and coworker‟s safety. It also has given some insight on the status of safety and health among the respondents. With the problems and perception of safety and health has been identified among the agricultural sectors, the study will help future research to provide appropriate recommendations to improve the workplace safety and health.